Deep-learning assisted iterative multi-objective optimisation of yarn production process. (26th February 2021) - Ghosh, Tamal; Martinsen, Kristian
In textile industries, ring and rotor spinning activities are most crucial to the yarn production process, which consist of many parameters and responses. To optimise the said process, the optimal settings for the process parameters must be obtained. Multi-objective optimisation models for yarn production exist but these are product sensitive and expensive in terms of the computation and production cost. In this article, an iterative multi-objective deep-learning assisted optimiser is developed and a non-dominated search technique is employed to obtain the Pareto optimal sets of the process parameters, which could improve the yarn quality. Further a Kohonen's self-organising map (KSOM)-based model is introduced to investigate the correlations among the yarn production variables. The proposed method is successfully validated with case studies and shown to outperform the existing results.